PENEGAKAN HUKUM TERHADAP AKSI UNJUK RASA YANG MENIMBULKAN KERUSAKAN PADA FASILITAS UMUM - Dioba Akdemart Sila Kharisudanya; Lusia Sulastri; Melanie Pita Lestari (JOURNAL OF LAW AND NATION, 2023)
In this study, the authors used a legal sociological approach, namely an approach that seeks to study law in a social context in order to understand the phenomenon of demonstrations that cause damage to public facilities in society. First, the author conducts legal studies in a social context related to individuals and society itself. Then the author conducts an analysis of the several sources of data obtained, namely, Primary Data is data that researchers obtain directly from news of demonstrations against the Job Creation Law which took place in anarchy, Secondary Data is data obtained from library research or literature studies. This studies provides recommendations so that people with self-awareness begin to increase their knowledge about how to express opinions in public properly and what laws and sanctions can be imposed on anyone who does not express opinions in public in an orderly manner & the consequences and sanctions that ensnare the prepetrators of destroying public facilities. In conclusion, this study concludes that the causes of demonstrations that have an impact on damage to public facilites can be caused by individuals, provocateurs and surrounding circumstances. Not only that, there are three efforts that are also carried out by the authorities, namely preemptive, preventive and repressive efforts. Thus, this research is expected to contribute to new understanding and knowledge and can be used as legal development in overcoming demonstrations that damage public facilities.